Immunological Mechanisms Underlying Atherosclerosis in Iraq: A Cross-Sectional Study - Auda, Shaimaa Awadh; Al-Dabis, Noor M. Jassim; Radhi, Zainb Awaad (American Journal of Biology and Natural Sciences, 2025)
Background: Atherosclerosis is a leading cause of cardiovascular morbidity and mortality in Iraq, with increasing prevalence in recent decades. While traditional risk factors contribute significantly to disease burden, the role of immunological mechanisms in the Iraqi population remains poorly characterized. This study aimed to investigate the relationship between specific inflammatory biomarkers and atherosclerotic disease severity in Iraqi patients. Methods: A cross-sectional study was conducted including 240 Iraqi participants (160 with confirmed coronary atherosclerosis and 80 controls). Blood samples were analyzed for inflammatory markers, including high-sensitivity C-reactive protein (hs-CRP), interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), and selected cell adhesion molecules. Coronary angiography findings were used to classify the severity of atherosclerosis. Demographic data, lifestyle factors, and comorbidities were recorded. Results: Patients with atherosclerosis demonstrated significantly elevated levels of hs-CRP (5.2±2.1 mg/L vs. 1.7±0.9 mg/L, p<0.001), IL-6 (7.8±3.6 pg/mL vs. 2.9±1.4 pg/mL, p<0.001), and TNF-α (18.3±7.5 pg/mL vs. 8.7±3.2 pg/mL, p<0.001) compared to controls. These inflammatory markers positively correlated with disease severity (r=0.68, 0.71, and 0.63, respectively, p<0.001). Multiple regression analysis identified IL-6 as the strongest independent predictor of severe atherosclerosis (OR=3.27, 95% CI: 2.14-5.02, p<0.001) after adjusting for traditional risk factors. Conclusion: This study provides evidence of distinct immunological profiles associated with atherosclerosis in the Iraqi population. IL-6 emerged as a particularly important inflammatory mediator, potentially offering both a biomarker and therapeutic target for addressing the growing burden of atherosclerotic disease in Iraq.